PRESERVING RELIGIOUS MODERATION LITERACY IN PESANTREN TAHFIDZUL QUR’AN AS-SUNNAH PARAPA NORTH GALESONG DISTRICT TAKALAR REGENCY - Abd. Karim; Wardiah Hamid; Muhammad Nur; Abu Muslim (Al-Qalam, 2021)
This article examined religious literacy in Pesantren Tahfidzul Qur’an As-Sunnah Parapa. Religious literacy is regarded as a forum for maintaining religious moderation and even strengthening religious moderation in Pesantren Tahfidzul Qur’an As-Sunnah Parapa, Takalar. The stigma of the veil is often a measure of how extreme a person is in religion. However, people at this pesantren are different from the veiled community in Galesong. They are very moderate and essential in overseeing religious moderation. They are very inclusive by building good relations with the local community, building educational institutions, prospering mosques, and building radio stations as a forum for da’wah. In addition, this article also examined the long journey of forming a settlement around Pesantren Tahfidzul Qur’an As-Sunnah Parapa. They were finally able to mingle with the local community with various approaches, although there were several rejections during the initial period of their arrival. The data were obtained through direct interviews with the local community. Data tracking and data processing were operated using qualitative research methods